Architecture of a mobile-agent of a distributed knowledge management system - Villareal, Pablo (2003)
This work describes a multi agent system designed to support the management of tacit knowledge that belongs to people of an organization. This is a distributed knowledge management system based on the use of mobile agents, which receive the user's queries and visit the organization domains where this information can be generated. The system has been developed using an approach based on the organizational concept of business processes to identify roles and protocols as part of the analysis stage of a methodology for agent-oriented analysis and design. The mobility of the agent is defined using an approach based on both the quality attributes specified for the multi-agent architecture and the execution environments of the multi-agent system. Particularly, this work is focused on describing the designed mobile agents’ architecture and some implementation details of it.